Estonian Animation : Between Genius and Utter Illiteracy - Robinson, Chris, 1967- (Book collections on Project MUSE., 2007)
Ever wonder why Estonian animation features so many carrots or why cows often perform pyramids' Well, neither question is answered in Chris Robinson's new book, Estonian Animation. Robinson's frank, humorous, and thoroughly researched book traces the history of Estonia's acclaimed animation scene from early experiments in the 1930s to the creation of puppet (Nukufilm) and cel (Joonisfilm) animation studios during the Soviet era, as well as Estonia's surprising international success during the post-Soviet era. In addition, Robinson writes about the discovery of films by four 1960s animation pioneers who, until the release of this book, had been unknown to most Estonian and international animation historians.